PENGARUH KOMPENSASI DAN DIKLAT TERHADAP MOTIVASI KERJA MELALUI PENGEMBANGAN KARIR ASN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BARRU - herman jaya; Ahmad Firman; Muhammad Hidayat (AkMen JURNAL ILMIAH, 2020)
The State Civil Apparatus is entrusted with three main tasks, namely providing services to the public, organizing general government, and carrying out development tasks. To carry out these three tasks the apparatus resource management plays a very important role. One function of human resource management is to increase employee motivation. Increased work motivation is influenced by several factors including compensation, education and training, and career development. The work motivation of the employees of the Public Works and Spatial Planning Office of Barru Regency has not been in line with expectations so that organizational goals do not achieve maximum results.The study aims to determine and analyze: 1) the direct effect of compensation and education and training on career development of the State Civil Service Office of Barru District Public Works and Spatial Planning, 2) the direct effect of compensation and training on work motivation of the State Civil Service Office of Barru District Public Works and Spatial Planning and 3) the indirect effect of compensation and education and training on work motivation through the career development of the State Civil Apparatus Office of Public Works and Spatial Planning of Barru Regency.The research approach is quantitative by using survey methods. The research was carried out at the Barru Regency Public Works and Spatial Planning Office for 2 (two) months, from October to November 2019. The study population was employees of the Barru Regency Public Works and Spatial Planning Office. Determination of the sample is done by saturation sampling technique (census), where the entire population of 82 people is used as a research sample. The data analysis technique used is path analysis.The results showed that: 1) compensation and education and training directly had a positive and significant effect on the career development of the State Civil Service Office of the Public Works and Spatial Planning in Barru District, 2) compensation and education and training directly had a positive and significant effect on the work motivation of the Apparatus State Civil Service of Public Works and Spatial Planning of Barru Regency, and 3) compensation and education and training indirectly have a positive and significant effect on work motivation through career development of the State Civil Service Office of Public Works and Spatial Planning of Barru Regency.